Perkembangan Asuransi Syariah di Inggris - Farhana Alfaruqi; Andi Prastowo (STAI Auliaurrasyidin Tembilahan, 2021)
Great Britain is a country where the majority of the population is non-Muslim, but the development of Islamic banking and finance is very good. This is evidenced by the operation of six full Islamic banks and sixteen banks that serve Islamic windows. Sukuk transactions for investors also increased as evidenced by increased demand on the London Stock Exchange with a total of £51 billion. Likewise with takaful products, the UK reinsurance market that deals in Islamic finance. As one of the largest insurance markets in the world, and a leading global center for wholesale insurance and reinsurance, the UK has the potential to support the growth of the takaful business in the years to come.